DEVELOPMENT OF UKRAINIAN CRYPTO INDUSTRY: FROM PRACTICAL EXPERIENCE TO DIGITAL LEADERSHIP - OPANASYUK, VITALY (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The urgency of the problem. The urgency of this topic is dictated by the strengthening of the global crypto lobby and the involvement of large and system capital in the crypto industry. Ignoring this fact can mean losing the investment race before it starts. High mobility and unlimited capacity of the crypto industry can be a good chance for Ukraine to know its niche in global cooperation.       Methods: methodological and informational basis of the work are: scientific works, materials of periodicals, internet resources, normative-legal acts.In the course of the research are methods of structural-logical analysis, comparison and generalization were used.Results: A number of tax and economic incentives for the development of cryptographic investment are proposed.  Directions of development in specialization and cooperation of Ukraine in the world crypt industry are offered.Scientific novelty: firstly identified and proposed the perspective, place and specialization of Ukraine in the interstate cooperation from the crypt industry point of view.Practical significance: The urgency of the topic is determined by the specialization and cooperation of Ukraine in the world of crypt industry and all significant opportunities that this young industry opens.  In addition, the willingness of private investors to take higher risks, comparing with classic investments, makes Ukraine one of the few areas that concentrates both unprofessional and professional investors.  That fact gives some benefits to the starting crypt industry development.First of them- to go through the formation of an expert layer,second- to form a group of professional investors and the third one- to explore the impact of cryptographic investment on GDP and competitiveness index.
Keywords: international specialization; crypto industry; mining; crypto investments; investments